Type 2 diabetes patients assessment of the COMODITY12 mHealth system. - Kardas, Przemyslaw; Lewandowski, Krzysztof (EAI Endorsed Transactions on Pervasive Health and Technology, 2015)
Background: Patient acceptance is one of the major barriers toward widespread use of mHealth. The aim of this study was to assess patients’ experience with their use of COMMODITY12 telehealth system. Methods: DM2 patients assessed COMMODITY12 system after its 6 weeks’ long use within clinical trial. Patients opinions were collected with 7-item questionnaire, assessing different aspects of system use, as well as EuroQol-5D-5L generic questionnaire, assessing health-related quality of life. Results: Thirty patients (female, 13, male, 17, mean age +/- SD 59.9 +/- 5.3) completed study. All dimensions of experience with system use were assessed well, with maximum values for clearness of instructions, and ease of use (4.80, and 4.63, respectively). Health related quality of life, as assessed with general utility measure, improved significantly (P
Keywords: mhealth; comodity12; diabetes